Current Dynamics and Water Column Stability in Indonesian Waters Based on Hydrodynamics Model - Engki Andri Kisnarti; Nining Sari Ningsih; Mutiara R Putri; Nani Hendriati (Indonesian Journal of Geography, 2021)
Monsoon currents and Indonesian Throughflow (ITF) have an essential role in the current Indonesian water system. The movement of current/water masses with non-uniform bathymetric conditions will affect the water column's stability in Indonesian waters. Therefore, this study aims to obtain the current dynamics and stability of the water column in Indonesian waters, based on a hydrodynamic model termed the HAMburg Shelf Ocean Model (HAMSOM). The results of the model are data of current, temperature, salinity, and density. The data is used to study the dynamics of seawater in Indonesian waters. The water column's stability is examined by calculating the Brunt Väisälä frequency values (N2) based on the density data generated. The results show that monsoon currents were stronger in shallow waters because the stratification did not change. Meanwhile, the maximum N2 value occurs at the surface to a depth of 80-100 m with a range of 0.0000-0.0006 cycle s-1. The study also produces an understanding of the condition of Indonesia's stability (N2 positive), both spatially and temporally.